2021
DOI: 10.46827/ejmms.v7i1.1169
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Motivation and Learning Performance in an Online Classroom With the Use of Neuromarketing

Abstract: In recent years, the newly emerging discipline of neuromarketing, which employs brain (emotions and behaviour) research in an organisational context, has grown in prominence in academic and practice literature. With the increasing growth of online teaching, COVID-19 left no option for higher education institutions to go online. As a result, students who attend an online course are more prone to lose focus and attention, resulting in poor academic performance. Therefore, the primary purpose of this study is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…Ref. [4] conducted a study aimed at understanding the potential of online classrooms to enhance learning performance with a sample of 297 students from Oxford Business College. This study utilized stimuli-based gaze analytics to assess the impact of short and long video lectures on student motivation and learning.…”
Section: Neuromarketing Research On Online Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Ref. [4] conducted a study aimed at understanding the potential of online classrooms to enhance learning performance with a sample of 297 students from Oxford Business College. This study utilized stimuli-based gaze analytics to assess the impact of short and long video lectures on student motivation and learning.…”
Section: Neuromarketing Research On Online Learningmentioning
confidence: 99%
“…These techniques have been widely applied to various educational tools, including website design, the creation of engaging educational materials and handouts, ebooks, and multimedia, which are of interest to contemporary educators. Based on the findings of Sola's [4] study utilizing facial coding and eye tracking software, it is suggested that academics incorporate visual shareable content every 4-5 min, utilize a visual board, and introduce class discussions to maintain student attention during long lectures. This is because prolonged lectures, exceeding 5.24 min, without shareable content result in decreased attention and poor recall and information retention.…”
Section: Levying Neuromarketing Research To Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation